The effect of different physical and sport activity courses on body image of Costa Rican students - Chacón Araya, Yamileth (2013)
The purpose of this study was to determine the effect of different types of physical education sport courses on perceived and desired body image in university students from the University of Costa Rica. Volunteers were 522 students (259 females and 263 males), registered in 13 different courses of sports classes, from which two categories were built: a) sports classes, and b) fitness classes. The subjects were measured for body variables (height, weight, and waist circumference) and with the values of height and weight the body mass index (BMI) was calculated. Students answered the body image scale by Thompson and Gray (1995) the first, second and last week of classes. Results indicated that there were no significant interactions in body image regardless of sex or different sports courses. Females had higher % body fat than males (p < 0.01), and their waist circumference increases slight, but significantly from pre-test to post-test compared to males (p < 0.05). Participants with higher % body fat also had greater body dissatisfaction scores (r = - 0.13, p < 0.01). In conclusion, there is no effect of the type of sport or fitness course on body image of university students; however, special attention should be placed for those students with increased adiposity as they showed greater dissatisfaction with their body image.